Traditional Tree Initiative: promoting Pacific agroforestry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Craig Elevitch describes how a series of fact sheets on CD-ROM is reacquainting Pacific islanders with local tree species.